2009
DOI: 10.1128/jvi.01143-09
|View full text |Cite
|
Sign up to set email alerts
|

Immune Evasion Proteins Enhance Cytomegalovirus Latency in the Lungs

Abstract: CD8 T cells control cytomegalovirus (CMV) infection in bone marrow transplantation recipients and persist in latently infected lungs as effector memory cells for continuous sensing of reactivated viral gene expression.Here we have addressed the question of whether viral immunoevasins, glycoproteins that specifically interfere with antigen presentation to CD8 T cells, have an impact on viral latency in the murine model. The data show that deletion of immunoevasin genes in murine CMV accelerates the clearance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 46 publications
2
7
0
Order By: Relevance
“…Importantly, partial inflation has been demonstrated in very young CMV-infected humans, whose CMV-specific CD8 T-cells develop T EM phenotypes but are not as inflated as elderly hosts [50], as well as adults whose responses (despite absolute magnitude) seem to be mostly T EM . Our findings are also consistent with murine work by others, including Andrews et al who showed the influence of viral load on magnitude of very early CD-8 T-memory responses in BALB mice [25], Bohm et al who showed correlation between tissue viral load and CD8 inflation in BALB mice [26], and finally work from Snyder et al who have shown similar dose dependent impacts on CD8 memory inflation in C57BL6 mice [15]. …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Importantly, partial inflation has been demonstrated in very young CMV-infected humans, whose CMV-specific CD8 T-cells develop T EM phenotypes but are not as inflated as elderly hosts [50], as well as adults whose responses (despite absolute magnitude) seem to be mostly T EM . Our findings are also consistent with murine work by others, including Andrews et al who showed the influence of viral load on magnitude of very early CD-8 T-memory responses in BALB mice [25], Bohm et al who showed correlation between tissue viral load and CD8 inflation in BALB mice [26], and finally work from Snyder et al who have shown similar dose dependent impacts on CD8 memory inflation in C57BL6 mice [15]. …”
Section: Discussionsupporting
confidence: 92%
“…Recent work by Reddehase et al has suggested that CD8 memory inflation after mCMV infection might be directly related to viral load [26]. If this is true, then based upon our T-cell results, we would expect to see significantly lower viral loads in mice infected with lower titers.…”
Section: Resultssupporting
confidence: 48%
“…What clearly supports this hypothesis is the murine model of CMV latency and reactivation postulated by Reddehase and his collegues (36,37). This model proposes that mouse CMV reactivation may occur independently for each latently infected cell and may be putatively defined by a random pattern of silenced and desilenced genes (1,21,42). Consequently, reactivation from latency can be regarded as a stochastic process, and the number of latent genomes cannot be estimated by analysis at a single time point.…”
mentioning
confidence: 89%
“…In the MCMV model, evasins interfere with antiviral protection through certain virus-specific T cells (62,63) and enhance viral latency (64), in the face of a paradoxically increased T cell response that is likely due to more efficient cross-presentation of viral Ag (65). In a rhesus macaque model, deletion of US2-11 does not alter the course of primary CMV infection but prevents superinfection of CMV-positive animals (66).…”
Section: Discussionmentioning
confidence: 99%